Development of the comprehensive method to manage risks in projects related to information technologies - Prokopenko, Tatiana; Grigor, Oleg (Eastern-European Journal of Enterprise Technologies, 2018)
A comprehensive method of project risk management is proposed for the field of information technologies based on the combined application of intelligent and expert methods under unstable conditions and constraints for financial and time resources. The method makes it possible to support making a decision based on the formalized technique of identification and estimation of risks, as well as the choice of the initial set of measures to avoid a risk event. This method was investigated based on the universal academic example of a project in the field of information technologies. The result of application of the comprehensive method of risk management is an improvement in the efficiency of an IT project by reducing losses in the project and overspending of financial resources. Risk model of an IT project based on the Bayesian network is developed, which is the base of the comprehensive method. A risk model of an IT project based on the Bayesian networks makes it possible to study different scenarios of risk occurrence by the simultaneous consideration of different factors in the external environment and internal state in the IT project, as well as their casual relations. The proposed model will make it possible to represent and estimate a risk probability for all possible scenarios and, accordingly, to develop effective measures for risk elimination. The proposed structure of the Bayesian network of an IT project risk could become a basis for the information technology of risk management in an IT project and an appropriate decision-making support system.